Opportunities and challenges of opening an independent nursing practice in Serbia - between law, market and professional initiative - Aritonovic, Nemanja; Jovcic, Ljiljana; Stojanovic, Goran R; Terzic, negra (Education and Research in Health Sciences, 2026)
Introduction: In an era marked by increasing challenges in healthcare systems worldwide including aging population, chronic diseases, and a shortage of healthcare professionals, the need to transform the role of nurses has never been greater. A healthcare system in which the nurse is not merely an executor but a holder of independent practice, autonomous, competent, educated, and accountable with their own clinic, patients, and decision-making zone, is a reality in many developed countries. In Serbia, however, this vision is only beginning to emerge, surrounded by legal ambiguities, institutional resistance, and market barriers.Aim: The aim of this paper is to explore the opportunities and challenges of establishing independent nursing practice in Serbia through the analysis of nurses’ attitudes and perceptions. Materials and Methods: A descriptive and observational indirect method was used in a survey. Results: The results indicate that nurses in Serbia recognize numerous obstacles in startingindependent practice, with the main challenges being the unfavorable legal framework, lack of institutional support, and financial barriers . At the same time, the majority of respondents express a high level of motivation and interest in this type of work, particularly in rural areas. There is a clear need for additional education and mentorship programs. When compared to European and global practices, Serbia shows a significant normative lag. Furthermore, a higher level of education positively correlates with greater readiness to initiate independent nursing practice. Discussion: The research showed that, although there is significant interest and willingness among nurses in Serbia to engage in independent nursing practice, numerous barriers still limit this opportunity in reality. The key barriers identified include an inadequate legal framework, lack of institutional support, low public and professional awareness, as well as the need for further education and financial support.
Keywords: independent nursing practice; nurses; legal regulation; professional challenges; healthcare